In Situ Synthesis of CNTs/Cu Nanocomposites and the Electronic Transport Properties. Issue 8 (27th February 2019) - Wang, Dongxing; Li, Da; Muhammad, Javid; Zhou, Yuanliang; Shah, Asif; Dong, Xinglong; Zhang, Zhidong
Abstract : Carbon nanotubes (CNTs)/Cu nanocomposite has been in situ fabricated by an arc‐discharge plasma approach. It is found that the herringbone‐bamboo‐shaped CNTs grow with assistance of Cu catalyst through an instantaneous vapor–liquid–solid (VSL) mechanism. Dielectric behavior dominates the electronic transport of CNTs/Cu nanocomposite, however, it is conductively modified by the metallic Cu nanoparticles, the residual catalyst exists in the nanocomposite. Temperature‐dependent resistivity of CNTs/Cu nanocomposite reveals that a transition from Mott–David (MD) variable range hopping (VRH) to Shklovskii–Efros (SE) VRH happens at the temperature of ≈10.7 K, which is further supported by theoretically calculated MD–SE crossover temperature T C = 10.6 K. The Coulomb gap Δ C = 0.14 meV is obtained for the CNTs/Cu nanocomposites, which is greatly significant to understand the conductive modification of CNTs by a metallic additive. Abstract : Herringbone‐bamboo‐like carbon nanotubes (CNTs)/Cu composite systems have been firstly fabricated by high energy arc‐discharge plasma. This approach is quite novel for in situ synthesis of carbon/metal nanocomposites. A transition of electronic transport mode from Mott–David variable range hopping (VRH) to Shklovskii–Efros VRH happens at ≈10.7 K with Coulomb gap Δ C = 0.14 meV.